Religiusitas Bhima dalam Teks Dewa Ruci - I Komang Widiana (Jurnal Yoga dan Kesehatan, 2019)
The text of Dewa Ruci tells about the journey of the character Bhima in carrying out hisswadarma as a student of Guru Drona to fulfill the task of finding tirtha amerta pawitra. From the story contained in Dewa Ruci’s text, it has a different or contradictory phenomenon between Bhima-Drona and tirtha amerta pawitra. Thus a more in-depth study is needed of the religiosity of Bhima’s figure on his journey in the literary work of Dewa Ruci from the point of view of Hindu Theology. Based on this description, in this study Bhima’s character in the Dewa Ruci Text as the object of research, entitled “Religiosity Bhima in Dewa Ruci Text (Study of Hindu Theology). The results of the study obtained in this study, that the religiosity of Bhima’s figure is reflected in Bhima’s journey which is a process of self-control and surrender. In addition, the journey of Bhima’s figure also reflects the holy journey which purifies him so that he is able to meet Hyang Dewa Ruci, in other words Bhima’s journey is a form of thirtayatra. As well as other theological teachings found in Dewa Ruci’s Textis the concept of pramana as a concept that supports living beings. By knowing this knowledge, it is hoped that Bhima as a depiction of humans can reach moxartham Jagadhitaya.